Determinants of male and female emotionality - Kornaszewska, Monika (Studia Psychologica: Theoria et praxis, 2002)
Contemporary research on human emotions concerning the significance of existing distinction between women and men are the main subjects of consideration presented in this article. The fundamental issue resolved at the basis of contemporary psychological research on both sexes is the question of the possibility of the emergence of two types of emotionality: famine and masculine. Categories of psychological phenomena distinguishing these two types of emotionality were separated on the basis of recent international research, i.e. emotional expression, emotional bonds with people, coping with difficult situations like stress and achieving success. Additionally, emotionality and sex differences are described from biological, psychical and social aspects, emphasising more the qualitative than quantitative ground of the proposed distinction. The described concept of creating the two types of emotionality could be used as a factor to explain mechanisms of human social functioning in a sense of building satisfactory i erpersonal relations. The research concerning this subject simultaneously with further theoretical consideration will be continued by the author of the article.